DESIGN OF ELECTRONIC-BASED HANDOUT TEACHING MATERIALS WITH PROBLEM-BASED LEARNING NUANCES IN LEARNING MATHEMATICS - Firman Aulia Ramadhan; Abd Muhith; Lailatul Usriyah (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2023)
This study is based on Permendikbud No. 65 of 2013, which mandates that students learn in accordance with 12 learning principles. As a result, educators must be adept at utilizing a variety of strategies to meet students' learning goals. Consequently, the purpose of this study is to assist teachers in utilizing a method that is in line with the curriculum, one of which is a problem-based learning method, in order to help students develop their critical thinking skills. So, in this study, problem-based learning, or a strategy that presents challenges connected to daily life in real terms, is used in the teaching materials created, namely E-Handout. To improve student motivation and learning results, interactive digital teaching resources have been developed. The study methodology employed is called ADDIE, which stands for Analysis, Design, Development, Implementation, and Evaluation. Analysis includes curriculum analysis, material analysis, and student analysis. Design includes handout design and material design, The systematics of Electronic Handout teaching materials are cover or title of the handout, KI/KD, learning objectives, concept maps, material and videos, exercises and quizzes, and bibliography.